Secure Transmission of Underlay Cognitive Radio with Passive Eavesdropping - Al-Nahari, Azzam; Al-Jamali, Mukarram; Alkhawlani, Mohammed (Dorma Trading Est., 2016)
The security in cognitive radio networks (CRNs) has attracted recently a significant attention due to the open environment of the spectrum sharing networks, which make them more vulnerable to wireless attacks. In this paper, we consider the problem of physical layer security in CRNs. Our objective is to enhance the secrecy performance of the secondary user (SU) in the presence of passive eavesdropper, whose channel state information (CSI) is unknown at the transmitter side. Two beamforming techniques are proposed; transmit beamforming (BF) and beamforming with jamming (BFJ). We investigate the impact of using artificial jamming (AJ) signal in improving the secrecy performance of the SU in underlay CRNs, where the AJ noise signal is used to confuse the eavesdroppers channel. Two power constraints are considered in the system; transmit power constraint and the interference power threshold at the primary user (PU). The performance of the proposed techniques is analyzed in terms of the achievable secrecy rate and the secrecy outage probability.